2014
DOI: 10.5761/atcs.oa.13-00278
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Thoracoscopic Surgery for Spontaneous Pneumothorax Using Multi-Degrees of Freedom Forceps

Abstract: Purpose: The objective of this study was to assess the perioperative results of a single-incision approach using multi-DOF forceps for spontaneous pneumothorax, in comparison with the traditional 3-port approach. Methods: Between May 2012 and June 2013, 44 patients with spontaneous pneumothorax underwent SITS, and their clinical characteristics and perioperative results were evaluated. We then compared those who had undergone SITS (SITS group) with those who had undergone traditional 3-port surgery before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Since then, some authors have reported SITS for PSP, and the adequacy of the technique has been discussed. [3][4][5][6][7][8][9] We have also established an original SITS procedure with a single incision 2.0 cm in length and have been using it in PSP patients since 2009. We herein describe the clinical characteristics and surgical results for the first 100 patients who underwent SITS for PSP.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, some authors have reported SITS for PSP, and the adequacy of the technique has been discussed. [3][4][5][6][7][8][9] We have also established an original SITS procedure with a single incision 2.0 cm in length and have been using it in PSP patients since 2009. We herein describe the clinical characteristics and surgical results for the first 100 patients who underwent SITS for PSP.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate the procedure, many authors have proposed the use of an articulated endograsper and a single-incision laparoscopic surgery device. 79 This is a dedicated wound protector having multiple channels, which facilitates maintaining a fixed position of the camera and working instruments, and reduces the risk of collisions between instruments during uniportal VATS. However, the single-incision laparoscopic surgery device has a higher cost than the standard wound protectors, and a relatively long skin incision is needed because the port should accommodate a minimum of three instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Gentle extrathoracic manipulation of the suture lifts the lesion and creates an angle that facilitates stapler wedge resection. Compared to previous methods, 713 our strategy does not need special devices; only a 0 suture and a sponge, widely available. Yet, as the suture traction is not accommodated within a uniportal incision, it does not interfere with the movement of other surgical devices inside or outside the thoracic cavity, facilitating handling and resection of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our institute performs uniportal thoracoscopic surgery for pneumothorax due to a fundamental belief of "reduced-port surgery." 4) This report describes a successful case of uniportal VATS anatomic segmentectomy through a 3.5-cm incision.…”
Section: Introductionmentioning
confidence: 99%